The Role of Technology-Mediated Feedback Pre- and Post-COVID-19 : A Case Study of First-Year Communication Students. - Lewis, Sally; McGill, Thai; Lim, Lisa-Angelique; Godwin, Rebecca (Journal of University Teaching & Learning Practice v.21 n.1 https://doi.org/10.53761/qrbshh97, 2024)
As universities welcome students who completed their secondary education during the disruptive period of the COVID-19 pandemic, it is timely to consider if their prior learning experiences influence receptiveness to technology-mediated communication. Australian Year 12 students struggled to stay motivated and connected with their learning during the pandemic, while also experiencing an increase in screen time of more than a day each week. Studies also indicate more secondary school students felt disengaged with online learning, likely due to the pandemic forcing them to learn online. This study explored commencing university student online activity and performance in a first-year course with technology-mediated communication in 2022 (n=118) and compared results with a similar pre-pandemic course in 2019 (n=192). Learning analytics data was used to create technology-mediated feedback based on student interaction with the course content and student learning experiences were evaluated. Course engagement data and a range of metrics were examined including the frequency of access to course information and assessment related content. Course performance data including final course grades and individual assessment results was also collected and examined. While an early outcome of research on post-pandemic technology-mediated communication, our findings suggest the 2022 student cohort were less receptive to technology-mediated feedback when compared to the pre-pandemic cohort. [Author abstract]